PENERAPAN PENDEKATAN SIKLUS BELAJAR (LEARNING CYCLE) BERORIENTASI KOOPERATIF UNTUK MENINGKATKAN HASIL BELAJAR - Faizul Bayani; Ida Wahyuni (IKIP Mataram, 2015)
This action research aims to improve student outcomes and learning processes. The population of this research was 32 grade X Gunungsari Vocational High School students, amounting to 32 people on the subject of atomic structure and periodic elements. The study was designed in three cycles and adjusted to the stages of Classroom Action Research (CAR). Instrument testing includes power test difference, level of difficulty and reliability. The results for cognitive aspects measured by the test increased from cycle 1 (77.42%) to cycle 2 (87.50%) but decreased in cycle 3 (56.25%), while affective aspects were measured by attitude questionnaires shows the average attitudes/responses of students in the good category and psychomotor aspects as measured by performance tests provide learning completeness of 100% with an average of 84.18. For the results of observations the teaching and learning process states that the activities of students are in the category of being quite active in cycle 1, active in cycle 2, and very active in cycle 3. Activity of teachers is in the very active category for all three cycles. Based on this data, it can be concluded that the implementation of cooperative oriented learning cycle approaches has a positive effect on the results and learning process of class X students at SMK 1 Gunungsari on the subject of atomic structure and periodic elements.